Analisis Perbandingan Penggunaan Activity-Based Costing Model dan Tradisional Model di Universitas Klabat - Koapaha, Hartini Pop (JBE (Journal of Business and Economics); Volume 10 No.2, 2011 JBE UNKLAB, 2011)
This research aims to analyze the difference of Traditional Method and Activity-Based Costing Method using in Klabat University for the period 2005-2010.  Also, it analyze the allocation of overhead cost at academic department, there are seven academic departments in this university such as economic department, education department, computer department, nursing department, secretary department, religion department and agronomi department. The difference between these two mothods using in this university with cost varience between traditional and ABC, for economic department is Rp. 858.474.616 or 52.78%, education department is Rp. 410.436.185 or 26.63%, computer department is Rp. 379.880.809 or 43.83%, nursing department is Rp.334.958.317 or 95.04%, secretary department is Rp. 117.773.298 or 23.37%, religion department is Rp. 183.930.388 or 21.94% and agronomi department was Rp. 58.045.382 or 22.50%. But when these two method compared and analyzed by statistical formula using t-test paired method, the difference between traditional costing and ABC costing was not significant difference, with standardiviation for tradisional method 8.53934 and for ABC method 8.95620, and the probability not more than 0.5 or two tail was 0.449.